Sobre a viabilidade de teorias infinitistas solucionarem o problema do regresso - Carneiro, Ana Stela Rossito (2019)
For many years the bare idea of a theory of justification based on infinite regress was precluded, or underdeveloped, for being grounded on an infinite chain of reasons. Infinitism had its beginning in the late 90’s with Peter Klein and still is a point of estrangement in the field of traditional philosophy. This dissertation aims to approach the aspects of Infinitists theories, as well the main objections, and evaluate the viability of them in solve the regress problem.